ANALISIS KUALIFIKASI SUMBER DAYA MANUSIA DALAM PENGELOLAAN RISIKO PADA PT ADHI KARYA (Persero) Tbk. - Yudha Astana, I Nyoman (Jurnal Ilmiah Teknik Sipil; Vol. 15, No. 2 Juli 2011, 2012)
In a construction project, a risk usually occurs during project planning, preparation, implementation and completion. Human resources as a part of a project risk management should have a proactive response to risks, whether it is the accuracy of perception or the methods used in responding to the risks. The human resources qualifications must be considered because it is related to the personnel who will manage a risk in a project. One important factor in the success of a project is the quality and competence of the personnel. It is necessary therefore, to evaluate the human resources qualification and factors contributing to the succesfully risk management in a construction project. Data were obtained from the project reports of PT. Adhi Karya (Persero), Tbk. They were analysed using Likert’s scale and statistical multiple linier regression. The software used was SPSS version 15. Based on the study results, the most influential qualification of risk management are education, working experiences in three projects risk management, working periods more than 6 years, and training experience at risk management.
Keywords: human resources, risk management.